Efficiency of 5-pegylated pamam G4.0 as a potential nano carrier for enhancing encapsulation fluorouracil - Tram Chau, Nguyen Thi; Chinh, Tran Hoang; Quyen, Tran Ngoc; Khoa, Nguyen Cuu (Vietnam Journal of Chemistry, 2015)
Polyamidoamine dendrimers are well-defined nano-structures exhibiting much cavity space inside which has been paid much attention in drug delivery. In the study, polyamidoamine dendrimer Generation 4 (PAMAM G4) was pegylated by nitrophenyl chloroformate-activated polyethylene glycol 4000-tyramine (NPC-PEG-TA). The pegylated dendrimer was characterized by NMR, FT-IR, GPC, and TEM, which revealed that G4-PEG4K’ MW is about 147,980 Da, and its size is ranging from 70 to 80 nm in diameter. The capacity of G4-PEG4K nanocarrier was evaluated in order to loading 5-Flourouracil (5-Fu) anticancer drug using HPLC. The results showed that G4-PEG4K can load 8.84 wt/wt% of the drug which is higher than that of G3-MPEG (around 6.28 wt/wt%). According this result, we can suggest that G4-PEG4K could be an effective nanocarrier for drug encapsulation. Keywords. Dendrimer, nanocarrier, anticancer drug, 5-Flourouracil.